Morphological, chemical, and crystallographic aspects of interface evolution in Al/Mg dissimilar friction stir welds - Usman Abdul Khaliq; Mohd Ridha Muhamad; Farazila Yusof; Suriani Ibrahim; Zbigniew Brytan; Takuya Miura; Tetsuo Suga; Yoshiaki Morisada; Hidetoshi Fujii (Journal of Materials Research and Technology)
Dissimilar friction stir welding (FSW) of aluminum and magnesium relies on mechanical interlocking and chemical bonding through intermetallic compounds (IMCs) forming at the interface. This study employed optical, scanning electron, and transmission electron microscopy for the microstructural characterization of AA6061/AZ61 welds at the nanoscale, made under optimized conditions. These were then used to explain the resulting mechanical properties. A new orientation relationship, [011‾0]Mg//[001]γ, (0002)Mg//(200)γ, between Mg and Al12Mg17, was identified based on a selected area diffraction pattern. High-resolution transmission electron microscopy revealed that for all three interfaces (Mg–Al12Mg17–Al3Mg2–Al), planes with high atomic density played a crucial role in the nucleation and growth of IMCs. In the stir zone, the microhardness of AA6061 decreased, as the softening effect outweighed the grain refinement's strengthening effect due to the dissolution of strengthening precipitates. This study's ultimate tensile strength (UTS) is 170 MPa, a value attributed to the mechanical interlocking provided by the transitional key-lock interface and a thin 1.4 μm IMC layer. Additionally, tensile fractures occurred in the Al12Mg17 phase, attributed to its inherent brittleness, which results from the retardation of slip caused by the covalent bonds between Al atoms within the crystal structure. A three-stage fracture mechanism has been proposed to elucidate the failure behavior of the specimens under tensile loading. This study contributes to the current understanding of interface evolution in Al/Mg friction stir welds and offers insights that could be applied to optimize microstructures for improved properties.